1997
DOI: 10.1007/s007050050216
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the Potyviridae with emphasis on legume-infecting potyviruses

Abstract: The 3'-terminal nucleotide sequences of thirteen authenticated strains of bean common mosaic virus (BCMV) and one strain of bean common mosaic necrosis virus (BCMNV) were obtained. The regions sequenced included the coat protein coding sequence and 3'-end non-coding region. These data, combined with sequence information from other legume-infecting potyviruses and the Potyviridae were used for phylogenetic analysis. Evidence is provided for delineation of BCMNV as distinct from BCMV and the inclusion of azuki m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 87 publications
0
26
1
6
Order By: Relevance
“…Previous phylogenetic analyses (6,16,27,29) of the genus Rymovirus used CP or partial NIb sequences to reconstruct evolutionary history. In these studies, AgMV and HoMV formed a clade with RGMV, whereas WSMV and BrSMV clustered in a separate clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phylogenetic analyses (6,16,27,29) of the genus Rymovirus used CP or partial NIb sequences to reconstruct evolutionary history. In these studies, AgMV and HoMV formed a clade with RGMV, whereas WSMV and BrSMV clustered in a separate clade.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Rymovirus (the type species is RGMV) currently includes these four mitetransmitted species plus Hordeum mosaic virus (HoMV [26]), for which a vector has yet to be identified, and several other virus species that have been partially characterized (19,36). Recently, based on analysis of coat protein (CP) and, in some cases, partial NIb sequences (6,16,27,29), it has been suggested that the genus Rymovirus is not monophyletic and should be split into at least two genera in which RGMV, HoMV, and AgMV remain within the genus Rymovirus, whereas WSMV and BrSMV constitute a new genus within the family Potyviridae (27). However, in previous efforts, <25% of the viral genomes were analyzed.…”
mentioning
confidence: 99%
“…Previous phylogenetic analysis of the family Potyviridae using 3 -proximal sequences have shown that terminal branches are long relative to internal branches with generally weak bootstrap support for dividing Potyvirus and Rymovirus taxa into independent clades [1,9,33]. Long branches are known to be problematic in phylogenetic reconstruction [7,13,29] and the data had other characteristics that may be expected to confound phylogenetic reconstruction such as varying degrees of alignment ambiguity, compositional heterogeneity, and large genetic distances among taxa [13,29,40].…”
Section: Retention Of the Genus Rymovirus Is Warrantedmentioning
confidence: 99%
“…Therefore reaction of these legume viruses on differentials may confuse the identity of a particular strain. Also most of the 'new' strains or 'novel pathotypes' identified by different workers do not behave as the traditional BCMV strains which were used for the selection of BCMV differentials [2,3]. Hence, the reliable criterion for differentiation of viruses/strains is molecular characterization of viral genome sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the reliable criterion for differentiation of viruses/strains is molecular characterization of viral genome sequences. Partial sequence data of the coat protein region can also be used to observe the variability in potyviruses [2,4]. The objective of this study was to characterize the BCMV strains prevalent in Himachal Pradesh using 3 0 terminal region of viral genome and to assess the utility of the region in strain differentiation.…”
Section: Introductionmentioning
confidence: 99%